Towards the Total Synthesis of Jerangolids – Synthesis of an Advanced Intermediate for the Pharmacophore Substructure. Issue 36 (17th September 2020) - Lenhof, Julian; Hutter, Michael; Huch, Volker; Jauch, Johann
Abstract : The jerangolids are a class of natural products with a skipped diene substructure isolated from Sorangium cellulosum . Here, we present a new strategy for the total synthesis of these compounds based on a skipped diyne as central building block and a suitably substituted epoxy aldehyde as building block for the dihydropyran substructure. So far, we reached an advanced intermediate which is related to the pharmacophore subunit of the jerangolids as well as of the ambruticins. A key step is a Shi epoxidation with high e.r . to form the epoxy aldehyde. Both building blocks are coupled in a Carreira alkynylation, where additional mechanistic studies based on DFT calculation were realized. The alkynylation is followed by a nucleophilic 6‐ endo ‐ tet epoxide opening to form the pyran structure and a Nicholas reduction to remove a propargylic OH group. Abstract : Here, we present a new strategy for the total synthesis based upon a skipped diyne as central building block. This was transformed so far into an advanced intermediate related to the pharmacophore of the jerangolids.